INTERNATIONAL LEGAL APPROACHES TO DISPUTE RESOLUTION IN GLOBAL BUSINESS ACTIVITIES - I Gede Riski Wirindranata (ADISAM Publisher, 2026)
International disputes often arise due to inconsistencies in the interpretation or implementation of international agreements. The two main issues raised are: 1) how to arrange the settlement of international business disputes according to international law? and 2) what are the forms of dispute resolution? This study adopts a normative legal method with a legislative approach. In the context of international business disputes, international law distinguishes between legal and political disputes, with solutions offered through courts such as the International Court of Justice (ICJ) or alternative settlement methods (ADR) such as arbitration, mediation, and conciliation. In Indonesia, arbitration, regulated by Law No. 30 of 1999, is a popular choice due to the final and binding nature of the decision, as well as the efficiency and flexibility it offers. Both methods, namely arbitration and mediation, are recognized in Indonesia, with arbitration providing legal certainty and mediation offering a cost-effective collaborative approach. In order to manage the risk of disputes and maintain good business relationships, governments need to strengthen regulations and infrastructure for international business dispute resolution and improve business people's understanding of these two methods, including integrating arbitration clauses in contracts.